Development and characterization of coffee-like brew from jackfruit (Artocarpus heterophyllus) seeds. - Debuque, Irene Joy Gentuya
Jackfruit (Artocarpus heterophyllus) is one of the most common fruit trees found in Southeast Asia, especially in tropical countries like the Philippines. The ripe fruit contains sweet yellow carpels which are widely used as desserts or ingredients in Asian culinary preparations. Ripe jackfruits are usually utilized for its pulp, while the seeds are being discarded. One whole fruit contains up to 500 seeds which make up around 10 to 15% of the total fruit weight. As a form of waste utilization, jackfruit seeds were roasted to produce a coffee-like brew. The raw seeds contained 8.93% protein, 49.68% ,oisture, and trace amounts of reducing sugar. Roasting was done in two treatments: medium and dark roast, with four time-temperature combinations in each treatment. The most preferred roast was determined by rank test for preference based on color. Kramer?s Rank sum Test at 0.05 level of significance showed that the four combinations in each treatment have a significant difference with each other. Mt1-T1 (100°C/20mins) was the most preferred combination for medium roast and Dt1-T1 (130°C/15 mins) was the most preferred for dark roast. The two roasting time-temperature combinations, Mt1-T1 and Dt1-T1 were prepared in six concentrations of jackfruit coffee-like brew namely, MC1 (10% medium), MC2 (14% medium), MC3 (18% medium), DC4 (10% dark), DC5 (14% dark), and DC6 (18% dark). The six brews were subjected to rank test for preference based on flavor and aroma. Kramer?s Rank sum Test at 0.05 level of significance revealed that the six brews have a significant difference with each other DC4 was determined as the most preferred jackfruit coffee-like brew. Physico-chemical analysis of the most preferred roast showed that the product has a mean moisture content of 2.12%, water activity of 0.08, and a pH 0f 6.26. Sensory evaluation of the most preferred jackfruit coffee-like brew indicated that the product has a chocolate-brown color and an aroma similar to plain, dark roasted coffee. The general acceptability test showed that the jackfruit coffee-like brew. Physico-chemical analysis of the most preferred roast showed that the product has a mean moisture content of 2.12%, water activity of 0.08 and a pH of 6.26. Sensory evaluation of the most preferred jackfruit coffee-like brew indicated that the product has a chocolate-brown color and an aroma similar to plain, dark roasted coffee. The general acceptability test showed that the jackfruit coffee-like brew was moderately liked. The paired comparison test revealed that the Arabica coffee was more bitter compared to the jackfruit coffee-like brew, but the latter was more preferred in terms of overall flavor and aroma. Physico-chemical analysis of the most preferred roast showed that the product has a mean moisture content of 2.12%, water activity of 0.08 and a pH of 6.26. Sensory evaluation of the most preferred jackfruit coffee-like brew indicated that the product has a chocolate-brown color and an aroma similar to plain, dark roasted coffee. The general acceptability test showed that the jackfruit coffee-like brew was moderately liked. The paired comparison test revealed that the Arabica coffee was more bitter compared to the jackfruit coffee-like brew, but the latter was more preferred in terms of overall flavor and aroma.